2012
DOI: 10.1093/brain/awr345
|View full text |Cite
|
Sign up to set email alerts
|

Reduced conduction failure of the main axon of polymodal nociceptive C-fibres contributes to painful diabetic neuropathy in rats

Abstract: Painful diabetic neuropathy is a common complication of diabetes mellitus and can affect many aspects of life and severely limit patients' daily functions. Signals of painful diabetic neuropathy are believed to originate in the peripheral nervous system. However, its peripheral mechanism of hyperalgesia has remained elusive. Numerous studies have accumulated that polymodal nociceptive C-fibres play a crucial role in the generation and conduction of pain signals and sensitization of which following injury or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 44 publications
7
65
1
1
Order By: Relevance
“…The data indicated that Nav1.7 was increased in diabetic neurons compared with controls, and the increases were also shifted accordingly in diabetic animals. These results were similar to the previous report that showed altered Na þ currents in diabetic neuropathy (Sun et al, 2012). Furthermore, GBP not only reduced Nav1.7 but also largely reversed the changes for activation of p-ERK1/2.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The data indicated that Nav1.7 was increased in diabetic neurons compared with controls, and the increases were also shifted accordingly in diabetic animals. These results were similar to the previous report that showed altered Na þ currents in diabetic neuropathy (Sun et al, 2012). Furthermore, GBP not only reduced Nav1.7 but also largely reversed the changes for activation of p-ERK1/2.…”
Section: Discussionsupporting
confidence: 92%
“…And the continuous GBP injection has been proven to be valid measures in our study. Many studies have reported altered excitability in DRG neurons, including small, medium and large neurons from a chronic compression disease (CCD) model and STZ-induced model (Huang and Song, 2008;Villiere and McLachlan, 1996;Sun et al, 2012;Tan et al, 2006). Similarly, our data demonstrated that DRG neurons from diabetic rats increase the excitability of neurons compared with the control.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Sodium channel α-subunits Na V 1.7 and Na V 1.8 are the 2 major subunits expressed by dorsal root ganglion neurons and are thought to play an important role in peripheral neuropathy in STZ-induced diabetic rats. 42 Here, we showed for the first time that STZ injection increased expression of Na V 1.7 and Na V 1.8 in DRGs. This is in agreement with previous reports that VGSCs have important roles in nociception and visceral pain.…”
Section: Discussionmentioning
confidence: 55%
“…It has been reported that abnormal hyperexcitability of primary sensory neurons contributed to the exaggerated pain associated with diabetic neuropathy (Hong et al, 2004a;Sun et al, 2012a;Jackson and Bean, 2007). It has been shown that Nav1.7 and Nav1.8 were over-expressed and the transient sodium current was increased significantly in small dorsal root ganglion (DRG) neurons in streptozotocin (STZ)-induced diabetic rats (Hong et al, 2004a;Sun et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%